Studies on X-Ray Diffraction, Thermogravimetric Stability, Antibacterial- Antifungal Activity of Fe(II), Ni(II), Cu(II) Metal Chloroquine Complexes Against Bacterial Strains and Fungal Spore - Kadam, Mukesh S.; Khiste, Sachin Atmaram; Dake, Satish Ashruba; Khade, Bhimrao Chintamanrao (Anti-Infective Agents, 2020)
Introduction: Synthesis of new coordination complexes has gained a great interest of the inorganic chemists as well as researchers. Methods: A literature survey has revealed that main group elements as well as transition metals with ligand like Schiff’s base and many drug have the ability to form a coordinate bond. 3d-series of metal complex with chloroquine as a ligand was synthesized (ML2) stoichiometrically and characterized by conductivity, melting point, UV-spectra, TGA and X-ray analysis of coordination complexes and anti-microbial activity. Results: The synthesized metal complex was evaluated for in vitro antibacterial and antifungal activity against the bacterial strains such as Plasmodium falciparum, Pseudomonas aeruginosa, E. coli, Streptococcus, Bacillus, Staphylococcus aureus and Aspergillus niger. Conclusion: The metal complex shows very potential antibacterial as well as antifungal activity like a commercial drug. Inorganic chemistry gives us good opportunities to use metal complexes as Pharmacological agents.
Keywords: chloroquine